2017
DOI: 10.1111/jsap.12613
|View full text |Cite
|
Sign up to set email alerts
|

Use of Oncept melanoma vaccine in 69 canine oral malignant melanomas in the UK

Abstract: Patients treated with the melanoma vaccine in our study had survival times similar to their counterparts receiving the vaccine in the USA. There were observed responses in patients with macroscopic disease and so the vaccine could be considered as palliative treatment in dogs with stage IV disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 29 publications
2
41
0
Order By: Relevance
“…Because of the low statistical power due to small number and group heterogeneity, the authors proposed controlled studies to assess whether the addition of any adjuvant treatment to surgery, including immunogene therapy, is able to significantly prolong survival in cases of canine oral melanomas. A very recent paper[21] analyzing the outcome of 69 canine melanoma patients after human tyrosinase DNA vaccination, reported a median survival time of 455 d, a value that is similar to those published earlier[19,20]. Since the authors observed responses in patients with macroscopic disease, they suggest that the vaccine could be considered as palliative treatment in dogs with remaining tumors or recurrence.…”
Section: Antigen-based Immunogene Therapysupporting
confidence: 68%
“…Because of the low statistical power due to small number and group heterogeneity, the authors proposed controlled studies to assess whether the addition of any adjuvant treatment to surgery, including immunogene therapy, is able to significantly prolong survival in cases of canine oral melanomas. A very recent paper[21] analyzing the outcome of 69 canine melanoma patients after human tyrosinase DNA vaccination, reported a median survival time of 455 d, a value that is similar to those published earlier[19,20]. Since the authors observed responses in patients with macroscopic disease, they suggest that the vaccine could be considered as palliative treatment in dogs with remaining tumors or recurrence.…”
Section: Antigen-based Immunogene Therapysupporting
confidence: 68%
“…Canine melanoma is a chemoresistant tumour and adjuvant chemotherapy using mostly platinum agents failed to show any clinical benefits . In the last decade, the development of a xenogeneic melanoma DNA vaccine has shown some promising results in terms of safety, clinical response and survival, but needs further investigations with randomized controlled trials . Effective systemic therapies, including targeted therapies and immunotherapy are strongly needed to treat this cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The review found that dogs that received the vaccine did not achieve a greater progression-free survival, disease-free interval, or median survival time than dogs that did not receive the vaccine [28]. Similar results were obtained in a study conducted in the UK [29]. The vaccine was shown to induce a B-cell response, which is unlikely to limit melanoma progression.…”
Section: Discussionmentioning
confidence: 60%